Learn Asset Management based on PTPN 9 Case – Preliminary Overview of the Institution, the Function, and the General Business Assets - Soedarmawan Soewardi; Hitapriya Suprayitno; Ria Asih Aryani Soemitro (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
Asset Management in general and IFAM specifically is very important. The knowledge and science need to be developed step by step. PTPN-9 can be used as an excellent Case Study. A general overview was developed as a base for studying the AM in PTPN-9. PTPN-9 is a state-owned-enterprise, whose duty is to manage the business of yearly plantations and seasonal plantations (sugar-cane plantations and sugar factories), in Central Java. Practically, all of the yearly plantations and seasonal plantations (sugar factories) were started by the Dutch, since the colonialization era. As the first step, this paper observes the production assets, the product, and the market. As production assets, the enterprise has 15 yearly plantations and 8 seasonal plantations. As products, it has 7 consumption commodities, 10 commercial commodities, 8 agro-tourism objects, and 14 restaurants and coffees. The enterprise sells its products into the international market and the domestic market.